Prevalence of Gingivitis in Orthodontic Patients Aged 16 to 35 Years: A Prospective Study (Journal of Dentistry and Allied Science, 2025)
Background: Gingivitis is a prevalent oral health issue among orthodontic patients, often aggravated by the presence of fixed appliances and inadequate oral hygiene practices. Despite its significance, limited data exist on the prevalence of gingivitis in orthodontic patients in Bangladesh. This study aimed to determine the prevalence of gingivitis in orthodontic patients aged 16 to 35 years. Methods: A prospective cross-sectional study was conducted at the Department of Orthodontics, The Dental & Orthodontic Center, Shankipara, Coronation Road, Mymensingh, Bangladesh from January 2023 to December 2024, involving 73 participants selected through purposive sampling. Clinical examinations were performed to assess gingival health using the Gingival Index (GI) and Plaque Index (PI). Data were analyzed using SPSS version 23.0, with descriptive statistics and chi-square tests to evaluate associations. Results: The study found a high prevalence of gingivitis (68.5%) among 73 orthodontic patients aged 16–35 years. Mild gingivitis was observed in 47.9% of participants, while 20.6% had moderate to severe gingivitis. Significant associations were noted between gingivitis and poor oral hygiene (p < 0.05) and longer treatment duration (>12 months, p < 0.01), highlighting the need for preventive measures during orthodontic care. Conclusion: The study highlights the high prevalence of gingivitis among orthodontic patients, emphasizing the need for improved oral hygiene practices and preventive measures during treatment. By maintaining proper oral hygiene and using inter-dental aids, one can significantly reduce the risk of gingivitis. Journal of Dentistry and Allied Science, Vol. 8 No 1: 28-33